Penerapan Sistem Informasi Electronic Costumer Relationship Management - Heri Purwanto; Amartya F Iswahyudi; Haikal Pirous; Dewi Indrawati (Masoem University, 2021)
E-CRM is customer management in electronic-based companies, dealing with complex management, attracting customers, and business partners through various media, including online and offline media, personal contacts, and other electronic communication media. E-CRM enables companies to better understand customer behavior and forecast customer needs through online activities, and can increase profitability. At PT. Suwanda Karya Mandiri has a problem with how to keep customers using the services of a technical consultant. Therefore, the initiative was taken to make it easier for customers who want to be interested in technical efforts and resources in an effort to keep customers using the services of technical consultants. To compete with competitors, the company implements E-CRM strategy to be able to establish good relationships and maintain customer satisfaction. In this study, the method used is the Prototype Method. The software used to develop E-CRM at PT. Suwanda Karya Mandiri uses Odoo software. Odoo software is software for business management. Based on the results of the test, it can be ascertained that using Odoo software and E-CRM can facilitate transactions between customers. This system can be further developed by implementing other modules such as Sales, Point of Sale, and Invoicing which can better assist PT. Suwanda Karya Mandiri.